'I already know what I learned': young children's perspectives on learning through play. Issue 10 (2nd October 2016) - Colliver, Yeshe; Fleer, Marilyn
ABSTRACT: Around the world, if and how young children learn through their play in early childhood education and care contexts has been the subject of much debate. Yet rarely has the debate heard from the young children themselves, often due to the pervasive belief that they do not understand learning. To redress this, a qualitative case study was conducted on 28 two–five-year-olds' perspectives about what they believed they were learning through play. Some 772 comments on learning in 683 episodes of play were analysed using cultural–historical theory, revealing how children as young as two are authorities on their own learning. Findings challenge popular ways of understanding young children's thinking and provide educators with concrete means to understand children's perspectives, learning and how educators can more effectively guide play towards learning outcomes, as expected in contemporary curriculum frameworks across the globe.